THE STATE OF STOCKBREEDING IN UZBEKISTAN IN 1917-1941 (on the example of the horse population) (Scientific journal of the Fergana State University, 2023)
This article provides a detailed analysis of the situation and problems of animal husbandry in Uzbekistan in 1917-1941, in particular, issues related to horses and horse breeding in the Republic, based on archival sources.